Pengaruh Edukasi Bahaya Rokok Elektrik Terhadap Tingkat Pengetahuan Remaja di SMA Negeri 3 Manado - Nurlela Hi Baco; Kristine Dareda; Devitatoby N. Sanangka (Jurnal Kesehatan Amanah, 2024)
Electronic cigarettes or Vapes are the evolution of conventional cigarettes or tobacco into electronic cigarettes, and the renewal of tobacco cigarettes into modern cigarettes which convert liquid into vapor. The purpose of this research was to find out the effect of education on the dangers of electronic cigarettes toward the level of knowledge of adolescents at SMA Negeri 3 Manado.Research was carried out using a pre-experimental method with a one group pre and posttest research design. The taken sample was 38 respondents using purposive sampling technique. The research instrument used was the Questionnaire Sheet of the dangers of electronic cigarettes. Furthermore the collected data was analysis used the Nemar MC test with a significance level (α) = 0.05. The research results showed that the highest age frequency was 12-16 years, 35 respondents (92.1%), gender for woman, namely 19 respondents (50.0%), and gender for man, namely 19 respondents (50.0%). From the results of the Nemar MC test, the P value = 0.016 with a significance <0.05, which means that Ha is accepted and Ho is rejected. The conclusion of this research is that there is an effect of education on the dangers of electronic cigarettes toward the level of knowledge of teenagers at SMA Negeri 3 Manado. It is hoped that the results of this research can increase teenagers' knowledge about the dangers of e-cigarettes.